Estimation of leopard population size in a secondary forest within Malaysia's capital agglomeration using unsupervised classification of pugmarks. - Sanei, Arezoo; Hussin, Mohamed Zakaria; Yusof, Ebil; Mohamad Kasim, Mohamad Roslan (Cambridge University Press (CUP), 2011)
The objective of this study was to estimate the population size of common leopard (Panthera pardus) in Ayer Hitam Forest Reserve in Selangor, Malaysia. Long term survival of leopard population in this area is threatened due to small size of the forest, isolation and presence of various disturbances in the habitat. However, no estimates are available on the number of leopard in the study area. We used unsupervised classification of pugmarks that allows clustering of the data sets based on their inherent similarities. Study was conducted during February to November 2008. Linear measurements of front and hind tracks and strides (n = 124) were classified using hierarchical cluster and discriminant analysis which indicated that at least four individuals of leopard were present in the study area of 1,411 ha. Despite the small size of the forest, the area is still rich in both fauna and flora. The leopard being the predator, has an important role in maintaining the health of the ecosystem. Therefore, the population size of the leopard could be used as indicator of sustainable conservation and management of the species in the area.